The Analysis of Science Literacy Ability and Teachers' Capability in Implementation of Learning by Science Literacy Oriented in Islamic Kindergarten at Bangko City - Siti Aisyah; Minnah El Widdah; Sukarno Sukarno (Postgraduate, University of Mataram, 2021)
This study aims to determine the analysis of scientific literacy skills and the ability of teachers in developing science literacy-oriented learning in Islamic Kindergartens in Bangko City. This study uses a quantitative approach with survey techniques. Data analysis was carried out by means of quantification on each measured aspect and continued with descriptive analysis. Based on the data and discussion as described above, at the end of this study it can be concluded that in general the ability of Islamic Kindergarten teachers in Bangko City is evenly distributed in each category. The scientific literacy ability of teachers with category